Inclusion through Exclusion How Young Immigrant Israelis in the Nationalist Yisra'el Beitenu Party Read Israeli Citizenship - Schmidt-Kleinert, Anja (Edition Politik, 2018)
How do young people from immigrant families become engaged in politics? Anja Schmidt-Kleinert examines the case of young Israelis who are actively engaged with the nationalist Yisra'el Beitenu party, led by the Israeli minister of defence, Avigdor Lieberman. She explores how the activists present Israeli citizenship in a way that is exclusionary to non-Jewish citizens and analyses their strategy to actively construct a sense of belonging to Israeli society or, more precisely, to the Jewish collective by (re-)producing the ethno-nationalist discourse.